Development of a Science Textbook Contextualized with Local Food Crops for Plant Classification to Enhance Science Teachers' PCK-Based Instructional Planning - Suriwahyuni, Suriwahyuni; Harsono, Tri; Gultom, Endang Sulistyarini (Lembaga Teewan Journal Solutions, 2026)
This study aimed to develop and evaluate a science textbook contextualized with local food crops on plant classification to enhance science teachers’ instructional planning based on the Pedagogical Content Knowledge (PCK) framework of Morine-Dershimer and Kent. The textbook was designed as a professional learning resource integrating content knowledge, pedagogical knowledge, curriculum knowledge, assessment knowledge, knowledge of students, and contextual knowledge. It consists of nine chapters, including seven chapters representing the PCK components and reflection worksheets to support teachers in analyzing teaching experiences and making pedagogical decisions. The study employed the 4-D development model (define, design, develop, and disseminate). Participants were 14 junior high school science teachers in Langkat Regency selected through purposive sampling. Product quality was evaluated through expert validation, while practicality and effectiveness were assessed using teacher responses and pretest–posttest analysis. The textbook demonstrated high validity, with expert feasibility scores ranging from 90.00% to 92.65% and Aiken’s V values between 0.67 and 1.00. Practicality reached 95.26%. Effectiveness testing showed a significant improvement in teachers’ instructional planning ability, with mean scores increasing from 39.33 to 48.33, supported by a paired-sample t-test (p < .001) and an average N-Gain score of 0.562 (moderate category). These findings indicate that the developed textbook is a valid, practical, and effective resource for supporting PCK-based science instructional planning.